PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, FINANCIAL LEVERAGE DAN KEPEMILIKAN MANAJERIAL TERHADAP PERATAAN LABA - Desi Ayu Rahmawati, 13.05.52.0222; Nuswandari, Cahyani (Students Journal of Accounting and Banking, 2018)
This study examines the effect of firm size, profitability, financial leverage and managerial ownership to income smoothing. This research was conducted at a manufacturing company listed on Indonesia Stock Exchange (BEI). Sampling method using purposive sampling with observation period 2014 to 2016 the number of samples obtained as much as 216. The analysis tool used is logistic regression with SPSS 18 program. The type of data used is secondary data. The results showed that the profitability and managerial ownership effect on income smoothing. While the size of the company and financial leverage does not affect the income smoothing.Keywords: firm size, profitability, financial leverage, managerial ownership and income smoothing